Genotyping of field strains of canine parvovirus in Haryana using PCR and RFLP - J, SAVI; P, MINAKSHI; G, PRASAD (The Indian Journal of Animal Sciences, 2011)
Canine parvovirus (CPV) is the causative agent of enteritis and myocarditis in young pups. Since there was no earlier report on the prevalence of CPV in Haryana, the present study was undertaken. The 50 canine parvovirus suspected faecal samples collected from veterinary hospitals were subjected to VP2 gene based PCR. Of these 33 (66%) were positive for canine parvovirus in Haryana. To characterise the canine parvovirus positive samples, PCR-RFLP was done using RsaI. The PCR-RFLP indicated that all the field virus strains detected in our study were either CPV-2a or CPV-2b type which differed from vaccine strain (CPV-2) currently in use. It demonstrated the potential application of RFLP to differentiate the CPV-2 antigenic variants. The presence of CPV even in vaccinated dogs, possibly suggests the vaccination failure.